Envelhecimento e cárcere: olhar do homem idoso encarcerado no contexto prisional. - Vilela, Daniely da Silva Dias (2025)
The general objective of this thesis was to analyze, based on the Bioecological Theory of Human Development, the development of elderly men incarcerated in the prison context. Specifically, the aim was to: 1) present the biosociodemographic data and the Mini-Mental State Examination (MMSE) of the participants; 2) analyze the person's characteristics and the impact of incarceration on proximal relationships, considering the microsystem, mesosystem, exosystem, macrosystem and chronosystem levels; 3) identify the feelings experienced by elderly men in relation to incarceration, as well as the needs perceived by them; 4) understand the factors that facilitate or hinder the development of the elderly in the prison context. This is a qualitative, cross-sectional, exploratory and descriptive research study, conducted with twenty elderly men serving sentences in prison institutions in Pernambuco. The data collection instruments included the Mini-Mental State Examination (MMSE), a bio-sociodemographic questionnaire and a semi-structured interview. Data evaluation was conducted through Thematic Content Analysis, following the stages of pre-analysis, exploration of the material, treatment of results and interpretation. The theoretical framework adopted - the Bioecological Theory of Human Development - allowed the analysis of the interaction between the four elements of the PPCT model (person, process, context and time) to understand the human development of the elderly incarcerated man. The results indicated that the participants, aged between 60 and 84 years, are mostly mixed race, with incomplete primary education or illiterate, of evangelical or catholic religion, and single or married. Only 35% are retired, with an income of one minimum wage, and have, on average, 4.6 children, who are visited by wives, daughters or sisters. The majority presented cardiovascular diseases, and impaired mental health, vision and hearing. The MMSE revealed a high rate of mild cognitive impairment, indicating the need for further investigation. Among the crimes committed, crimes against sexual dignity predominate, followed by homicide and drug trafficking, with sentences ranging from eight to 174 years. Feelings such as sadness, frustration, anguish, loneliness, lack of motivation, discomfort, humiliation and helplessness were reported; associated with the loss of freedom and disconnection from their identities, roles and families. The fundamental needs reported include health, privacy, own space, financial resources and social contact. The rupture with previous life and the failure to meet essential needs tend to interrupt the continuity of interactions and compromise human development. However, while many experience significant difficulties, others demonstrate resilience, adjusting to new situations and actively dealing with challenges. These results highlight the need for a prison environment adapted to the specificities of the elderly, in addition to adequate institutional assistance. Thus, meeting these demands is essential to promote the well-being, dignity and continuity of the development processes of this population. It is expected that the results will contribute to guiding professionals in the organization of projects aimed at promoting the quality of life and development of elderly people involved in crime, such as those incarcerated, or at risk of involvement. Furthermore, the aim is to contribute to mitigating the impacts resulting from the increase in the elderly population in prisons, by encouraging crime prevention policies and social and educational programs aimed at the reintegration of prisoners, with special attention to the Northeast region of Brazil, particularly in the state of Pernambuco.